PEMANFAATAN LIMBAH KOTORAN SAPI DAN LIMBAH ORGANIK RUMAH TANGGA SEBAGAI BAHAN BAKU PRODUKSI BIOGAS - Hardoyo, Hardoyo; Natalina, Natalina; Atmono, Atmono; Sulastri, Sulastri; Andika, Wahyu; P.nasoetion, P.nasoetion (Jurnal Bakti Masyarakat Manajemen, 2022)
Waste cow dung and organic waste is a source of household materials that can be used to produce biogas.In hamlet purwosar-2i, in natar, its, southern district the throw off impurities cattle and organic waste houses to the environment and do not understand that both the waste can be processed to be more value products, namely. biogasMany people did not know technically making biogas from both the waste.Hence the need to introduce lesson of both the waste into biogas.The purpose of this activity is to the understanding that waste cow dung and organic waste households can be converted into biogas products that can be used as alternative energy for cooking and megurangi pollution with his second. the wasteMethods used in this event are interactive exposure to small-scale, biogas production households and household organic-waste colud be use to biogas production.